Association Between Different Contexts of Physical Activity and Anxiety-Induced Sleep Disturbance Among 100,648 Brazilian Adolescents: Brazilian School-Based Health Survey - De Moraes-Ferrari, G (Elsevier Ireland Ltd, 2020)
Physical activity (PA) practice can be a protective factor for anxiety-induced sleep disturbance (AISD), however the association between different contexts of PA and anxiety-induced sleep disturbance is not clear. We aimed to analyze the association between different contexts of PA and AISD. Data from the Brazilian School-based Health Survey [n=100,648; age: 14.3y (range:11–18 years)], conducted in 2015, were used. Higher PA during transport was associated with higher AISD. PA during physical education classes presented lower odds for AISD. PA practiced outside school was associated with reduced AISD among boys. The association between PA and AISD seems to be context-dependent. © 2020 Elsevier B.V.